HER+ Stakeholder workshop paves the way for piloting Learning Labs in India - CGIAR Gender Equality Initiative (CGIAR Initiative on Gender Equality, 2023)
The CGIAR Gender Equality initiative, HER+ on 27- 28 November convened for a workshop with stakeholders who are playing a pivotal role in designing and piloting Socio-technical Innovation Bundles (STIBs) in learning labs in West Bengal and Odisha in India. This workshop was part of the process of co-designing and implementing STIBs. These bundles, designed collaboratively together with women farmers, aim to enable them to gain better access to climate-smart innovations that suit them best. This participatory approach ensures a strategic combination of social, technical, and technological innovations, meticulously tailored to address the diverse needs and perspectives of the communities.